The Digital Children Litrary Work: Seeing From Meaning Perspective - Girsang, Martina; Br Ginting, Elvina; Panduwinata, Gloria; Sihombing, Intan; Sinaga, Tomok (International Journal of Education and Digital Learning (IJEDL), 2023)
Literary works can certainly be enjoyed through anything, be it through books, poetry, drama, music and films. Literature children can also be enjoyed through films that are currently booming. Nowadays, you can enjoy it with your family in the cinema. Talking about children's literature, it has a big impact on both adults and children, because there are no limits to enjoying children's literature. What needs to be found is the meaning or purpose of a work that was created. Can it have a good impact on the recipient of the work or even become a bad impact. Many think that literature can only be enjoyed by children, even though children's literature does not have a minimum age or regardless of age, from children to parents can certainly enjoy it. There are many morals that can be drawn from children's literature, the more we know the meaning of a literary work, the more we can apply it in our lives.